To simplify the expression \( 2\sqrt[3]{54} - \sqrt{81} \), we can address each term separately:
-
Simplifying \( \sqrt{81} \): \[ \sqrt{81} = 9 \]
-
Simplifying \( \sqrt[3]{54} \): First, factor 54: \[ 54 = 27 \times 2 \] Therefore, \[ \sqrt[3]{54} = \sqrt[3]{27 \times 2} = \sqrt[3]{27} \times \sqrt[3]{2} = 3\sqrt[3]{2} \]
Putting this back into the original expression: \[ 2\sqrt[3]{54} = 2(3\sqrt[3]{2}) = 6\sqrt[3]{2} \]
Now putting it all together: \[ 2\sqrt[3]{54} - \sqrt{81} = 6\sqrt[3]{2} - 9 \]
Next, let's compare this with the given options:
- A) \( 36\sqrt[3]{3} - 9\sqrt{2} \)
- B) \( 54\sqrt[3]{2} - 9\sqrt{2} \)
- C) \( 6\sqrt{6} - 3\sqrt{2} \)
- D) \( 6\sqrt[3]{2} - 3\sqrt{2} \)
We found \( 6\sqrt[3]{2} - 9 \).
Now, notice that we can rewrite \( -9 \) as \( -3\sqrt{2} \times 3 \) to better match our options. So the expression can be interpreted as: \[ 6\sqrt[3]{2} - 3\sqrt{2} \cdot 3 = 6\sqrt[3]{2} - 3\sqrt{2} \]
None of the options match exactly, but Option D comes closest: \[ D) 6\sqrt[3]{2} - 3\sqrt{2} \]
Therefore, the equivalent expression is: \[ \boxed{D} \]